Validité de la modélisation objet dans la langue et dans la traduction / Aleksandra Żłobińska-Nowak. - Żłobińska-Nowak, Aleksandra
Słowa kluczowe: modeling object language, hierarchical semantic network, class of objects, word sense disambiguation, learning process.